"Be a Man": The Role of Social Pressure in Eliciting Men's Aggressive Cognition. (November 2021) - Stanaland, Adam; Gaither, Sarah
Threatening a man's manhood—but not a woman's womanhood—elicits aggression. In two studies, we found evidence that this aggression is related to the social pressure men experience to "be a man." In Study 1a, we conducted an exploratory factor analysis to isolate participants' ( N = 195; M age = 19.92) differential motivations for conforming to gender norms. Study 1b then showed that pressure to be masculine moderates the relationship between gender identity threat and aggressive cognition for men. In Study 2a, we conducted a confirmatory factor analysis to validate the aforementioned scales with an age-diverse sample of men ( N = 391; M age = 33.16, range = 18–56 years). Study 2b replicated Study 1b, most notably with younger men. In all, these findings reveal one pathway—the pressure men experience to be stereotypically masculine—that elicits aggressive cognition when under threat in a U.S. context.